Frequency of Vernal Keratoconjunctivitis Types in Patients Presenting to Tertiary Care Hospital - Mubashir Rehman, Jamal Hussain, Imran Ahmad, Adnan Ahmad, Mohammad Farhan, Jawad Humayun (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vernal keratoconjunctivitis (VKC) is a condition that affects both eyes at the same time, recurs at regular intervals, and is an allergic inflammatory reaction of the conjunctiva and cornea to a variety of chemicals. Amongst the various populations the prevalence of various types of VKC varies. Objective: To assess the frequency of vernal keratoconjunctivitis types in patients presenting to tertiary care hospital Methodology: The current cross sectional study was carried out at the Ophthalmology Department, Qazi Hussain Ahmad Medical Complex, Nowshera from March 2022 to August 2022. All the patients were assessed under slit-lamp for VKC and their types. IBM SPSS version 23 was employed for analysis of data. Results: In the current research, totally 150 patients were enrolled. There were 90 (60%) male patients while female patients were 60 (40%). Based on the types of VKC, 75 (50%) patients were observed with Palpebral VKC, 41 (27.33%) with Limbal VKC and 34 (22.67%) patients were observed with Mixed VKC. Conclusion: Our study concludes that Vernal keratoconjunctivitis is a common problem of children. Both males and females are affected by this problem but occur predominantly in male. The most prevalent type of vernal keratoconjunctivitis was Palpebral VKC in our study. Keywords: Frequency; vernal keratoconjunctivitis; Eye diseases